Analisis Karakteristik Wajik Dengan Modifikasi Perbandingan Konsentrasi Gula Pasir Dan Gula Aren - Dewi Arziyah; Ifta Azmi; Anwar Kasim (LPPM Universitas Dharma Andalas, 2025)
The purpose of this study was to determine the effect of adding various concentrations of palm sugar and granulated sugar on the quality characteristics of diamonds and to determine the most preferred concentration of palm sugar and granulated sugar based on organoleptic tests. This study used a completely randomised design with 5 treatments and 3 replications. Observations made in this study were organoleptic test, water content test, fat content test, and sugar content test. The results showed that the addition of palm sugar and granulated sugar to the diamond had a significant effect (significantly different) on aroma, texture, moisture content, and sugar content.